Implementation of Legal Remedies in Resolving Disputes Between Government Employees with Employment Agreements (PPPK) with Local Governments - I Nyoman Gede Remaja (International Journal Labs, 2023)
The existence of PPPK in the personnel system in Indonesia is not supported by adequate legal protection arrangements both in Law No. 5 of 2014 and in Government Regulation Number 49 of 2018 concerning the Management of Government Employees with Employment Agreements. The legal protection in question is related to dispute resolution efforts in the event of a dispute between the PPPK and government officials. Based on this, peneliti is interested in conducting research on the implementation of legal remedies in resolving disputes between PPPK and local governments. To find out directly the application of Article 129 paragraph (1) of Law No. 5 of 2014 related to pppk dispute resolution. The method used is a type of empirical legal research with a descriptive nature of research. The research was conducted at the Buleleng Regency Personnel and Human Resources Development Agency. Data collection techniques use documentation study techniques and interview techniques, with data analysis using qualitative data analysis. Legal remedies taken by PPPK in the event of a dispute between PPPK and the Government are through administrative efforts which include a. Attempted Objections: An objection to the KDP Decision can be submitted in writing to the KDP containing the reasons for the objection accompanied by supporting data, while the objection to the Officer's decision can be submitted in writing to the superior of the official who is authorized to punish by containing the reasons for the objection accompanied by supporting data and the copy is submitted to the official. The objection in question is submitted within a maximum of 14 (fourteen) working days from the date the decision submitted by the objection is received by the ASN Employee. B. Administrative Appeals: An administrative appeal is filed against the PPK's action or decision regarding the termination of the employment agreement as a PPPK and submitted in writing to the ASN Advisory Board containing the reasons and/or evidence of the objection and the copy is submitted to the KDP. Administrative appeals must be filed within a period of no more than 14 (fourteen) working days from the date the KDP Decision filed by the administrative appeal is received by the ASN Employee.